Changes in the accounting scenario – new procedures: asset recoverability test approach (Revista Brasileira de Contabilidade e Gestão, 2013)
The convergence between the Brazilian Accounting Legislation and the International Accounting Standards may be considered one of the most debated subjects in the areas of Accounting, Economics and Law due to the innovations it presents to the Brazilian context. The goal of this article is to discuss the impairment test as a tool of capital evaluation. It is a basic study that follows the model of an exploratory research with the use of bibliographical studies. The discussions carried out allow us to infer that, taking into consideration the whole of modifications in Accounting norms and procedures, and aiming at a better adjustment of methods of control and evaluation, the impairment test is coherent as a procedure to evaluate the assets. Such changes in the Accounting scenario require training processes so that the professional of Accounting may adopt the international standards in the organizations in a short time.
Keywords: international norms; Brazilian Accounting Legislation; impairment test